Recurrence of Primary Aldosteronism 10 Years After Left Adrenalectomy for Aldosterone-Producing Adenoma: A Case Report - Kong, Linghui; Zhang, Jin; Dong, Lei; Xu, Jianzhong; Gao, Ping-Jin; Wang, Ji-Guang; Zhu, Limin (Frontiers in Endocrinology, 2021)
A 29-year-old female patient diagnosed with primary aldosteronism (PA) in 2004 underwent complete adrenalectomy for left aldosterone-producing adenoma (APA) confirmed by hematoxylin and eosin (HE) and CYP11B2 staining. Her hypokalemia was corrected, and her blood pressure (BP) normalized and maintained without medication for 10 years. In 2014, her BP became elevated again, and a recurrence of PA with an adenoma on the right adrenal gland was discovered by computed tomography scan. She underwent partial right adrenalectomy in 2018 due to unsatisfactory BP control with medication and gradually enlarging adenoma. The resected adrenal tissue contained a CYP11B2 staining positive APA. Her BP was then controlled by two drugs. Sanger sequencing of DNA extracted from tissue slices revealed that both left and right adenomas carried the same aldosterone-driver KCNJ5 gene mutation, but with different nucleotide changes. We suggest that patients who undergo adrenalectomy for APA should be followed up for life.